Benefit of [18F]-FDG PET/CT for treatment-naïve nasopharyngeal carcinoma - Yang, Shan-Shan; Wu, Yi-Shan; Chen, Wei-Chao; Zhang, Jun; Xiao, Su-Ming; Zhang, Bao-Yu; Liu, Zhi-Qiao; Chen, En-Ni; Zhang, Xu; OuYang, Pu-Yun; Xie, Fang-Yun (European journal of nuclear medicine and molecular imaging, 2022)
Background To test the advantages of positron emission tomography and computed tomography (PET/CT) for diagnosing lymph nodes and staging nasopharyngeal carcinoma and to investigate its benefits for survival and treatment decisions. Methods The performance of PET/CT and magnetic resonance imaging (MRI) in diagnosis was compared based on 460 biopsied lymph nodes. Using the propensity matching method, survival differences of T3N1M0 patients with ( n = 1093) and without ( n = 1377) PET/CT were compared in diverse manners. A radiologic score model was developed and tested in a subset of T3N1M0 patients. Results PET/CT performed better than MRI with higher sensitivity, accuracy, and area under the receiver operating characteristic curve (96.7% vs. 88.5%, p < 0.001; 88.0% vs. 81.1%, p < 0.001; 0.863 vs. 0.796, p < 0.05) in diagnosing lymph nodes. Accordingly, MRI-staged T3N0-3M0 patients showed nondifferent survival rates, as they were the same T3N1M0 if staged by PET/CT. In addition, patients staged by PET/CT and MRI showed higher survival rates than those staged by MRI alone ( p < 0.05), regardless of the Epstein-Barr virus DNA load. Interestingly, SUVmax-N, nodal necrosis, and extranodal extension were highly predictive of survival. The radiologic score model based on these factors performed well in risk stratification with a C-index of 0.72. Finally, induction chemotherapy showed an added benefit ( p = 0.006) for the high-risk patients selected by the model but not for those without risk stratification ( p = 0.78). Conclusion PET/CT showed advantages in staging nasopharyngeal carcinoma due to a more accurate diagnosis of lymph nodes and this contributed to a survival benefit. PET/CT combined with MRI provided prognostic factors that could identify high-risk patients and guide individualized treatment.